The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0244145
|View full text |Cite
|
Sign up to set email alerts
|

Age influences on Propofol estimated brain concentration and entropy during maintenance and at return of consciousness during total intravenous anesthesia with target-controlled infusion in unparalyzed patients: An observational prospective trial

Abstract: Purpose Aging affects pharmacodynamics/pharmacokinetics of anesthetics, but age effects on Entropy-guided total intravenous anesthesia with target-controlled infusions (TIVA-TCI) are not fully characterized. We compared aging effects on effective estimated brain concentration of Propofol (CeP) during TIVA-TCI Entropy-guided anesthesia, without neuromuscular blockade (NMB). Methods We performed an observational, prospective, single-center study enrolling 75 adult women undergoing Entropy-guided Propofol-Remif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Even if the impact of physiological changes on the pharmacokinetics/pharmacodynamics of anesthetic drugs as well as on ABM observed with aging [ 76 , 77 , 78 ] was postulated to influence explicit and implicit memory formation [ 79 ], in our study, aging seems not to be a risk factor for implicit memory occurrence. The age-induced decline of implicit memory (e.g., priming) is less than the decline of explicit memory (e.g., recognition) [ 79 ].…”
Section: Discussionmentioning
confidence: 51%
“…Even if the impact of physiological changes on the pharmacokinetics/pharmacodynamics of anesthetic drugs as well as on ABM observed with aging [ 76 , 77 , 78 ] was postulated to influence explicit and implicit memory formation [ 79 ], in our study, aging seems not to be a risk factor for implicit memory occurrence. The age-induced decline of implicit memory (e.g., priming) is less than the decline of explicit memory (e.g., recognition) [ 79 ].…”
Section: Discussionmentioning
confidence: 51%
“…The Eleveld TCI model also showed a higher bias in Predictive Median Performance Error (MdPE) than the Schnider one in older patients, probably contributing to higher DAEs and BSEs in older subjects [5]. Despite aging producing alterations in cardiovascular physiology that increase the onset time of anesthetic drugs [32], an increase in sensitivity to the hypnotic drug in the elderly compared to adults [11] may exacerbate the effect of equilibration between plasma and effect site concentration and favor deep anesthesia events during TIVA-TCI in elderly patients, in particular BSEs [33], which deserve attention due to being related to postoperative delirium and neurocognitive disorders [21,34]-although this is still debated [35][36][37]. Furthermore, aging was shown to impact the depth of anesthesia monitoring and EEG-based monitoring systems; different studies have shown higher indices in elders than in young people under a comparable anesthetic plan [33,38].…”
Section: Discussionmentioning
confidence: 99%
“…Despite aging producing alterations in cardiovascular physiology that increase the onset time of anesthetic drugs [32], an increase in sensitivity to the hypnotic drug in the elderly compared to adults [11] may exacerbate the effect of equilibration between plasma and effect site concentration and favor deep anesthesia events during TIVA-TCI in elderly patients, in particular BSEs [33], which deserve attention due to being related to postoperative delirium and neurocognitive disorders [21,34]-although this is still debated [35][36][37]. Furthermore, aging was shown to impact the depth of anesthesia monitoring and EEG-based monitoring systems; different studies have shown higher indices in elders than in young people under a comparable anesthetic plan [33,38]. Modulating the rate of propofol infusion after anesthesia induction on the basis of a difference between the expected and measured BIS, as in the Eleveld model which uses BIS as the measure of effect [2], may increase the risk of hypnotic overdosage and result in deep anesthesia events, particularly in elderly patients [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 The unreliability of commonly used sedation scales in conditions where the patient is nonresponsive due to muscle relaxation leads to various objective methods of assessment. The objective methods of assessing sedation in mechanically ventilated patients are Bispectral Index (BIS), 8 Entropy, 9 Narcotrend, 10 and others.…”
Section: Introductionmentioning
confidence: 99%